Theoretical Foundations of Romanticism Research in the Art Studies of the 20th – 21st Centuries: Ukrainian Perspective - Lihus, Olha (Journal of History Culture and Art Research, 2020)
In the globalization era characterized by the fusion of cultural traditions of different nations, there is an alternative tendency within the humanities: the increasing focus on the problem of national-stylistic specificity of the past and present artistic phenomena. Romanticism – an artistic style that dominated the European culture in the period of 19th – the beginning of the 20th centuries that inspired the freedom of national spirit’s expression and artists’ interest in folklore and historical past of their nation is a demonstrative example of such phenomena. The article deals with the historiographical aspect of Romanticism research in the humanities (in particular, philosophical, cultural, musicology, and literature studies) basing on the works of European, American, Russian, and Ukrainian scholars of the 20th – 21st centuries. Much attention is given to the musicological conceptions of Romanticism that are considered in the broad context of the interdisciplinary field of Romantic historiography. Moreover, the analysis and evaluation of the scientific achievements of the Ukrainian scholars that examine this topic hold a valuable place in the research’s presentation. Basing on the analysis of these works, the causes of multiple interpretations of Romanticism are defined and their representatives’ common grounds are specified: the consideration of Romanticism as a multidimensional category, recognition of Romanticism’s national versions in different European cultures, perception of Romanticism as a dynamic system of multidirectional tendencies. Finally, the contemporary approaches in the Romanticism research are outlined.